2020
DOI: 10.35808/ersj/1897
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Eco-Innovation Performance: Evidence from European Countries

Abstract: Purpose: The aim of the paper is twofold. Firstly, it attempts to assess the spatial pattern of eco-innovation performance in European countries and to identify economies which are efficient in transforming eco-innovation inputs into outputs. Secondly, it endeavours to examine eco-innovation efficiency distribution and existence of spatial externalities across European countries. Design/Methodology/Approach: The sample consists of 21 European countries. We use two eco-innovations inputs and two eco-innovation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The spatial heterogeneity and impact mechanisms of green innovation found in this paper are also present in other developed and developing countries such as Europe [77], Finland [78], and Myanmar [79]. In the context that sustainable development has become a global consensus, both the UK, US, Australia, Japan, Sweden, Belgium, and developing countries such as India, Iran, Malaysia, Vietnam, Turkey, and Egypt are generally under pressure to transition to sustainable development.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The spatial heterogeneity and impact mechanisms of green innovation found in this paper are also present in other developed and developing countries such as Europe [77], Finland [78], and Myanmar [79]. In the context that sustainable development has become a global consensus, both the UK, US, Australia, Japan, Sweden, Belgium, and developing countries such as India, Iran, Malaysia, Vietnam, Turkey, and Egypt are generally under pressure to transition to sustainable development.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, Corradini said that green technology patents are very unevenly distributed among European countries [76]. Kijek and Matras-Bolibok pointed out that countries with high and medium-high eco-innovation capacity are in northern and central-western Europe, while those with medium-low and low eco-innovation capacity are in central-eastern and southern Europe [77]. It can be seen that the spatial cluster and spatial differences exhibited by green innovation are geographic phenomena common to different regions and different countries.…”
Section: Theoretical Valuementioning
confidence: 99%
“…In addition, Corradini said that green technology patents are very unevenly distributed among European countries [76]. Kijek and Matras-Bolibok pointed out that countries with high and medium-high eco-innovation capacity are in northern and central-western Europe, while those with medium-low and low eco-innovation capacity are in central-eastern and southern Europe [77]. Caratù and Mazzanti et al also suggested that green technology patents are significantly more in northern Italy than in other regions [78].…”
Section: Theoretical Valuementioning
confidence: 99%